(untitled) (Research, Society and Development, 2020)
American Tegumentary Leishmaniasis is a disease of chronic evolution, caused by protozoa of the genus Leishmania, its transmission to man, occurs by the bite of sand flies (Diptera: Psychodidae). The research aimed to study the incidence of human cases of American Tegumentary Leishmaniasis (LTA) in the south of the State of Roraima in the municipalities of São João da Baliza and São Luiz do Anauá. This study describes 68 cases of (ATL) in humans that occurred in two municipalities in both locations, detected and registered between 2003 and 2005, whose identification and diagnosis were carried out at the National Health Foundation (FNS) and the Department of Health of the State. As for the incidence of ATL for the study, it was 49 cases for the municipality of São João da Baliza and 19 for the municipality of São Luiz do Anauá. As for entomological collection, light traps were used in housing and forest areas in both municipalities. This study may support strategies that will contribute to the creation of models of environmental controls and occupational guidelines in the work process in the region.